Gestión técnica de riesgos laborales en la línea de armado 4 de la empresa SEDEMI SCC - Naula Apugllón, David Marcelo (2023)
Summary In the context of the line of research in Engineering, Industry and Production, a study was carried out focused on occupational risk management in assembly line 4 of SEDEMI SCC. This process was structured in three essential phases. The first consisted of the identification of hazards, carried out through an on-site inspection and specific checklists for the four jobs involved. The second stage addressed the risk assessment, for which three different methodologies were applied: the method proposed by the National Institute of Safety and Health at Work (insst), NTP 330 and the Mathematical Evaluation Method of William T. Fine . Finally, the third phase focused on the proposal of preventive interventions, aimed at those risks categorized as moderate, important and intolerable. Within this framework, continuous improvement actions were proposed on health and safety issues. These included the review and modification of the SST policy, a SWOT analysis, the evaluation of stakeholder expectations, the development of a professional profile model and the formulation of specific indicators for SST management. As a result of the analysis, it was determined that the welder position is the one that faces the greatest exposure to significant risks. Among these, noise, working at heights and exposure to gases and non-ionizing radiation stand out. Keywords: Occupational risk, danger, evaluation, control, NTP 330, insst, William Fine.